Serum immune indicators including IgM, IgA, and IgG levels and quality of life of patients with gastrointestinal tumors during chemotherapy: Serum immune indicators in cancer - Wang, Yunlong (Journal of Medical Biochemistry, 2025)
Objective: This research attempted to clarify impact of dietary intervention on nutritional status, immune indicators including IgM, IgA, and IgG levels, and quality of life of patients with gastrointestinal tumors during chemotherapy.Methods: The 100 patients with gastrointestinal tumors undergoing chemotherapy in our hospital from January 2023 to June 2024 received selection and division into a control group (CG) and a study group (SG) according to different nursing methods, with 50 cases each. The CG received conventional chemotherapy nursing intervention, and SG received dietary nursing on the basis of conventional nursing in CG. The nutritional indicators including body mass index (BMI), oral mucosal cell apoptosis rate, hemoglobin (HGB), and serum albumin (ALB) levels, immune indicators including IgM, IgA, and IgG levels and quality of life before and after nursing between both groups received comparison.Results: After nursing, BMI, oral mucosa cell apoptosis rate, HGB level, and serum ALB level in both groups exhibited elevation relative to those before nursing, and SG exhibited elevation relative to CG (P < 0.05); IgM, IgA, and IgG levels in both groups exhibited elevation relative to those before nursing, and SG exhibited elevation relative to CG (P < 0.05); physical functioning scores, social functioning scores, psychological functioning scores, and material life scores in both groups exhibited elevation relative to those before nursing, and SG exhibited elevation relative to CG (P < 0.05).Conclusion: Providing dietary nursing intervention for patients with gastrointestinal tumors during chemotherapy can effectively facilitate their nutritional status, enhance immune function, and improve their quality of life.
Keywords: Gastrointestinal tumors; chemotherapy; dietary intervention; nutritional status, immune function